2020
DOI: 10.1002/slct.202000796
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Furo[3,2‐c]coumarin Derivatives through Multicomponent [4+1] Cycloaddition Reaction Using ZnO/FAp as a Sustainable Catalyst

Abstract: An efficient green protocol is developed for the synthesis of ten new furo [3,2-c]coumarin derivatives employing zinc oxide loaded on fluorapatite (ZnO/FAp) as catalyst. The threecomponent one-pot condensation occurs between the 4hydroxycoumarin, isocyanide and selected aldehyde in ethanol solvent at room temperature. Excellent yields (94-98 %) of target products in 16-20 min reaction time is the attractive feature. As-synthesized catalysts and organic compounds were fully established by powder-XRD, TEM, SEM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Optimization. We initially examined the alkylation of 1-methoxy-4-phenylpyridinium tetrafluoroborate (1a•BF4) with 2cyclohexylbenzo-[d] [1,3,2]dioxaborole (CyBCat) as a model system. [34] Methoxypyridium salt 1a•BF4 was prepared by oxidation of 4-phenylpyridine with m-CPBA followed by methylation with the Meerwein's salt (Me3OBF4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization. We initially examined the alkylation of 1-methoxy-4-phenylpyridinium tetrafluoroborate (1a•BF4) with 2cyclohexylbenzo-[d] [1,3,2]dioxaborole (CyBCat) as a model system. [34] Methoxypyridium salt 1a•BF4 was prepared by oxidation of 4-phenylpyridine with m-CPBA followed by methylation with the Meerwein's salt (Me3OBF4).…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic heterocyclic compounds, especially nitrogen containing rings, are core elements of vitamins, amino acids, nucleic acids, and alkaloids and thus attract the attention of the synthetic community and the pharmaceutical industry since many years. [1] A recent study has shown that 59% of U.S. FDA approved smallmolecule drugs contain a nitrogen heterocycles. [2] Their late-stage functionalization is of great interest to modify and tune their pharmaceutical properties.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, tetrabutylammonium bromide (TBAB) can be used to catalyze the reaction of 4-hydroxycoumarin with ethyl benzylidenecyanoacetate to synthesize pyrano [3,2-c]coumarin derivatives (Scheme 1b). 22 There have been many related reports on synthetic methods for these compounds using many catalysts, such as metal catalysts (Fe, Cu, Pd), [23][24][25][26][27][28] NaBr, 29 ZnO, [30][31][32] hexamethylenetetramine, 33 and potassium phthalimide. 34 The major disadvantages of using these catalysts are unsatisfactory yields, long reaction times, complicated operations, and high cost.…”
Section: Examples 40-93% Yieldmentioning
confidence: 99%
“…On the other hand, multicomponent reactions (MCRs) have steadily gained significance in synthetic organic chemistry [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. MCRs offer many benefits—e.g., greater yields, high atom efficiency, reduced reaction time, high convergence, minimisation of purification requirements and waste generation—compared to multiple-step syntheses [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%